ATİPİK REFLEKS SEMPATİK DİSTROFİ SENDROMLU BİR OLGU - KOÇ, Filiz; ZORLUDEMİR, Suzan; YERDELEN, Deniz; BOZDEMİR, Hacer (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Reflex sympathetic dystrophy syndrome is a disorder characterized by pain, edema, discoloration and autonomic abnormalities. Its etiopathogenesis is not completely determined. A 31-year-old male was admitted to our department with complaints of edema, pain, motion limitation and skin color changes in his right foot and ankle of it that is started 3 months ago. He had a history of recurrent ulcers in the mouth for 3 years and working in cast iron factory for 19 years, and we learned that the same limb of him was exposed to a trauma. In neurological examination; paresis, hypoesthesia, allodynic and hyperpathic pain were detected in the right lower limb. Electrophysiological study showed mixt type polyneuropathy. Heavy metal intoxication, collagen tissue diseases, endocrinopathies and malignant conditions were excluded. Although there was a history of a mild trauma to that limb and we know that nerve injuries play a role in the etiopathogenesis of reflex sympathetic dystrophy syndrome, a question comes to the mind about whether polyneuropathies can cause this syndrome.